2021
DOI: 10.31219/osf.io/zy9dv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are there non-linear relationships between alcohol consumption and long-term health?: A systematic review of observational studies employing approaches to improve causal inference

Abstract: Research has long found ‘J-shaped’ relationships between alcohol consumption and certain health outcomes, indicating a protective effect of moderate consumption. However, methodological limitations in most studies hinder causal inference. This review aimed to identify all observational studies employing improved approaches to mitigate confounding in characterizing alcohol–long-term health relationships, and to qualitatively synthesize their findings (PROSPERO registration: CRD42020185861). Eligible studies met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Of the 11 protocols describing use of a structured tool, Ibrahim 84 and Verdiesen 85 planned to use STROBE-MR 32 , 33 and other published literature, including the MR guidelines by Davies, 21 LS Lee 26 planned to use a self-developed questionnaire (also included in our synthesis of tools) based on published guidelines including Davies, 21 Grover 27 and Burgess. 20 Markozannes 99 planned to use a self-developed tool based on the results of the main analysis and of the sensitivity analysis; Naassila 100–102 planned to use Q-GENIE; 25 Shi 105 , 106 planned to use a modified version of a recently developed tool (no reference provided); Visontay 112 , 113 planned to use the tool developed by Mamluk; 28 and Wong 115 planned to conduct risk-of-bias assessment based on the guidelines from Davies. 21 Of the seven protocols describing a MR-specific risk-of-bias/quality-of-evidence assessment without using a structured tool, four planned an assessment based on the literature: Grover, 80 , 81 Jiang 86 and van Oort 111 referred to the MR methods protocol published by Grover 27 and Julian 87 did not report any reference.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 protocols describing use of a structured tool, Ibrahim 84 and Verdiesen 85 planned to use STROBE-MR 32 , 33 and other published literature, including the MR guidelines by Davies, 21 LS Lee 26 planned to use a self-developed questionnaire (also included in our synthesis of tools) based on published guidelines including Davies, 21 Grover 27 and Burgess. 20 Markozannes 99 planned to use a self-developed tool based on the results of the main analysis and of the sensitivity analysis; Naassila 100–102 planned to use Q-GENIE; 25 Shi 105 , 106 planned to use a modified version of a recently developed tool (no reference provided); Visontay 112 , 113 planned to use the tool developed by Mamluk; 28 and Wong 115 planned to conduct risk-of-bias assessment based on the guidelines from Davies. 21 Of the seven protocols describing a MR-specific risk-of-bias/quality-of-evidence assessment without using a structured tool, four planned an assessment based on the literature: Grover, 80 , 81 Jiang 86 and van Oort 111 referred to the MR methods protocol published by Grover 27 and Julian 87 did not report any reference.…”
Section: Resultsmentioning
confidence: 99%
“…This approach can address many of the limitations of conventional cohort studies (see Table S1 in the online supplement). Our recent review identified a single study applying MSMs to the alcohol-depression relationship (24). In a sample aged 20-64, Gemes et al found a U -shaped relationship with major depression after 7-9 years of follow-up (25).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Harmful drinking is responsible for substantial disease burden globally, 10 and there is evidence that inflammation may mediate the increased risk heavy drinking brings for a range of health outcomes. 11 However, as is the case for many conditions to which alcohol consumption is thought to contribute pathophysiologically, 12 some research suggests that compared to abstaining, lower levels of drinking may actually be beneficial when it comes to inflammation. [13][14][15][16][17] This is typically indexed via levels of inflammatory markers such as high-sensitivity C-reactive protein (hsCRP) -widely used by the clinical and research communities due to its stable expression in response to elevated proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%